COMBATING POVERTY THROUGH POLICIES OF DECENTRALIZATION -CASE OF VLORA CITY, ALBANIA - Veliu, Matilda (Journal of Advanced Research in Law and Economics; Vol 1 No 2 (2010): JARLE volume 1 Issue 2(2) Winter 2010, 2017)
Poverty is one of the main problems with which are facing developing countries. Despite the potential sources that they have, interior and external factors which influence a lot in the development of the country, play in this point of view a significant role in the problem. Thinking about the social and monetary costs of the problem, it’s normally to say that always, this problem will be in focus of the political strategies made by government. Decentralization, as a potential accelerant in the process of economic growth of the country, may have a positive impact in reducing the poverty. The process requires an analysis of that country's labour market, the actual phase of the decentralization process, the optimal coordination of inputs so, that impact of the process will be effective and efficient. Something it’s sure, not always decentralization will give the desired results, may even aggravate the situation still further, reducing the standard of living of citizens. Thus, it’s necessary to find new strategies or new opportunities which could provide positive returns for citizens.
Keywords: poverty, decentralization process, economic costs, labour market